SELEKSI BEBERAPA GENOTIPE PADI SAWAH LOKAL (Oryza sativa L.) TERHADAP CEKAMAN KEKERINGAN MENGGUNAKAN POLYETHYLENE GLYCOL (PEG) PADA FASE PERKECAMBAHAN - Shinta Sawitri; Robbana Saragih; Ervina Aryanti (Jurnal Agroteknologi, 2018)
Rice paddy (Oryza sativa L.) is important and main food plant in Indonesia. The problems field cultivation rice paddy in wetland is declining ground water availabity and uncertain climate change. The research was carried out with the aim to get the rice paddy local from the Kuok district, regency Kampar that is resistant to the condition of the grasp of drought in the phase of germination. The research was conducted in November-December 2016 at Pathology, Enthomology and Microbiology laboratorium and experimental field State Islamic University of Sultan Syarif Kasim Riau. Experiments were prepared using a completely randomized design factorial the first factor were 10 genotypes rice paddy local and the second factor was solution PEG concentration 6000 0% and 20%. Parameters observed that the germination (%), vigor index, crown length increment (cm), root length of wax coating (cm), and the number of penetrating root of wax coating. Based on result analysis of tolerance index recapitulation from five variables observation parameters there are nine genotypes that are tolerant to drought stress and one genotype susciptible to drought stress